Methylene Blue Adsorption by Using Eggshells in Synthetic Solution - Abu Bakar, Norhaliza; Ally Irdina Najid Afendi,; Mustaza, Nurin Nabilah; Bahman, Nur Alia Arisa (Multidisciplinary Applied Research and Innovation, 2021)
The amount of methylene blue dye released into the textile industry's wastewater is increasing throughout the year, and this problem is concerning. There are many side effects of having dye released into the wastewater, such as eutrophication, which can be the source of algal blooms that affect the aquatic organisms because of the lack of oxygen in the water and the environment too. This research focuses on reducing the amount of methylene blue dye released into the wastewater by using the adsorption method and using the eggshells as the adsorbent. The batch study used different adsorbent dosages (0.2g, 0.4g, 0.6g, 0.8g and 1.0g) and different particle sizes of adsorbent (0.30mm, 0.60mm, 1.18mm, 2.36mm and 5.00mm). It is expected that the higher the adsorbent dosage used, the higher the dye removal efficiency and the smaller the particle size used, the higher the dye removal efficiency. This study's contribution to eggshells' methylene blue adsorption shall get a future assessment in a prospective wastewater treatment facility setting.